Can AI Support Remote Prenatal Monitoring? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Traditional prenatal care, while a cornerstone of modern medicine, faces significant challenges in providing continuous, equitable, and proactive support to ...
Keywords: Telemedicine and Digital Health; Support; Remote; Prenatal; Artificial Intelligence; Machine Learning; Healthcare